Rlationship between deglutition, oral reflexes and articulatory ability of the cerebral palsied - PetuaM. Vaz (Journal of All India Institute of Speech and Hearing)
There are controversial views regarding the relationship between deglutition, oral speech reflexes and articulation in the cerebral palsied. Some authors are of the view that there is no relationship between these 3 variables (Hardy, 1933; Ingram, 1962; Hixon and Hardy, 1964; Bosma, 1975). However others opine that these 3 variables exhibit some inter-relattjon (Mysak, 1959; Shepperd, 1964; Gallender, 1979; and Love, Hagerman and Taimi, 1980).